Pecularities of evaluating methodology of learning and education of adults - GUTU, Vladimir (Acta et Commentationes, Sciences of Education, 2023)
Adult learning and education can be seen as the fourth pillar of lifelong learning – alongside school education, professional training and higher education. Adult learning and education falls under the general forms of education: formal, non-formal and informal, being predominantly of a non-formal and informal nature. This system allows any adult to develop personal and professional skills, thus becoming an active member of society. The methodological framework for adult learning and education in this system is a main component, but the establishment of a mechanism for evaluating its theoretical and procedural approaches is an indisputable condition for ensuring the quality of learning and formal and non-formal education of adults. The proposed concept is based on two dimensions: the evaluation of methodology of learning and education of adults as a science and part of andragogy and the evaluation of methodology of learning and education of adults as a set of strategies and didactic methods aimed at the formation in adults of certain competences, determined by their needs. A mechanism for evaluating the respective methodology in both dimensions is also proposed.